PENGARUH MEDIA PEMBELAJARAN PAPAN PANCASILA TERHADAP PEMAHAMAN SISWA MATERI MENGENAL LAMBANG SILA PANCASILA FASE A SEKOLAH DASAR - Munawaroh, Fa'izatul; Irianto , Apri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Pancasila board learning media on student understanding of the material of recognizing the symbols of the Pancasila precepts. The research method used is an experiment with a posttest only control group design. The data collection technique used in this study was through tests. The use of tests in this research is in the form of 10 objective questions which are used to measure the presence or absence of students' understanding abilities which are then analyzed by statistical tests using SPSS version 26. The results of this study indicate that there is a significant effect of using the Pancasila board learning media on students' understanding of the material of recognizing the symbols of the Pancasila precepts. The researcher concluded that the Pancasila board media is effectively used in learning material to recognize the symbols of the Pancasila precepts to improve students' understanding ability.